Does Intellectual Capital Improve On The Performance Of SME’s ? - Reni Shinta Dewi; Taher Alhabsy; Zainul Arifin; Yusri Abdillah (Sekolah Pascasarjana Universitas Brawijaya, 2019)
The purpose of this study is to analyze the affect of intellectual capital on performance for SMEs through competitive advantage. This is important, because intellectual capital is a strategic resource for SMEs. The study was conducted on two biggest clusters of batik industry in Central Java namely Pekalongan and Laweyan Solo. The sample consists of 149 SMEs with respond rate 74,5%. The results show that all dimensions of intellectual capital directly affect the competitive advantage, human capital directly affects the performance. Meanwhile structural capital and relational capital indirectly affect the performance. Sobel test shows that the affect of structural capital Â and relational capital toward performance through competitive advantage, it means that competitive advantage of perfect mediates. This finding is in line with the Knowledge based view, which states that intellectual capital as an intangible capital that can create value and enhance competitive advantage that will lead to organizational performance. Limitations of this study that the concept of intellectual capital was a relatively new concept, especially for SMEs, so that subjectivity perceptions of respondents are still very strong so it needs to be studied more in the factors that build intellectual capital in order to obtain other capital that characteristic of SMEs. For further research, it is necessary to include another capital such spritual capital and social capital in order to develop a intellectual capital for SMEs